Umanizzazione delle cure: curare con l'arte - Francesco Burrai; Giovanni Salis (AboutScience Srl, 2020)
Art can be a way, together with Nature, to intercept that landscape and inner climate characterized by the rhythm of silence. That dimension of iridescent calm imbued with creative and vital energy, which pushes towards a universal, seductive, profound sphere. Man can, with courage, abandon himself in this harmony and melody of thoughts that suggest a vast and visionary possibility. Each person has the inner possibility to be Art, to get out of the continuous distortions of daily life, to produce a metamorphosis of one's life. Art triggers the unconscious side of seeing, a rhythmic, dynamic principle, on which every gesture of maximum spontaneity depends, not touched by the artificial, by masks of fugacity and by false personalities. Without Art, it seems that part of real life is missing. The deep artistic power is fluid, without space or time, pulsating with new forms and substance and creating a new personal identity, contiguous to the real world, which inspires new desires. Many diseases of today and yesterday are produced by the lack of expressiveness or by the repression of personal creativity. Art produces well-being because it is the transformation of unconscious expressive energies, so life for our health.